2017
DOI: 10.1111/resp.13175
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic fibrosis score predicts survival in systemic sclerosis‐associated interstitial lung disease

Abstract: A high radiographic fibrosis score was a poor prognostic factor in SSc-ILD. More widespread fibrosis was associated with an increased risk of death, independent of HRCT pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 25 publications
(36 reference statements)
0
40
0
2
Order By: Relevance
“…Quantifying the extent of fibrosis has yielded important information including prediction of pulmonary function decline 21 and risk for mortality 5,22,23,24 . Advances in quantitative measurements of fibrosis 25 has allowed HRCT to become a valuable tool for detecting response to treatment.…”
Section: Hrctmentioning
confidence: 99%
“…Quantifying the extent of fibrosis has yielded important information including prediction of pulmonary function decline 21 and risk for mortality 5,22,23,24 . Advances in quantitative measurements of fibrosis 25 has allowed HRCT to become a valuable tool for detecting response to treatment.…”
Section: Hrctmentioning
confidence: 99%
“…Takei et al could demonstrate in confirmation of known evidence (11,12) that a high fibrosis extension score is associated with an increased risk of death, and further independent from HRCT pattern (13). In this context reduced HRCT might qualify for the visual scoring of lung fibrosis extension as no difference to standard HRCT was found and could be used as a follow-up examination in monitoring and therapy management of patients with SSc-ILD.…”
Section: Discussionmentioning
confidence: 61%
“…Different studies have shown that the extent and severity of ILD can be adequately assessed using visual scales (3,6,8). Further the extension of fibrosis is evidently associated with an increased risk of death (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality risk has been reported to be higher in patients with a disease extent of at least 20% on HRCT (10-year survival was 43% versus 67%, respectively, in patients with disease extent above versus below the 20% threshold) 60 . Similarly, a high fibrosis score on HRCT (based on the extent of reticulation and honeycombing) has been associated with increased mortality 61 . Large esophageal diameters are associated with increased ILD severity and decreased DLCO 48 .…”
Section: Prognosismentioning
confidence: 99%